PENERAPAN SURAT PEMBERITAHUAN ELEKTRONIK (E-SPT) MASA PPN TERHADAP PEMENUHAN PEMERIKSAAN PADA WAJIB PAJAK BADAN (STUDI KASUS KPP MADYAMAKASSAR) - Amran Amran; Rezki Wardani; Andi Rustam (Jurnal Riset Perpajakan: Amnesty, 2020)
The purpose of this study is to answer the problem of how to implement an online service system, namely the application of electronic notification letters (E-SPT) which is carried out on tax audit compliance in accordance with Parker's theory (2011: 1) in the form of optimal information or optimal information services such as availability. , easy to understand, relevant, useful, timely, reliable, accurate and consistent. The basis of this research is a qualitative descriptive type of research. The techniques used in data collection are field observation, in-depth interviews, and documentation. Then the data and interview results obtained were analyzed descriptively qualitatively. From the results of the research conducted, it shows that there is data stating that the process of implementing an Online-based System for the fulfillment of the inspection has been implemented properly, it is proven that there is a very synchronous answer between service informants and tax audit informants and shows consistency by requiring all taxpayers to be registered at KPP Madya Makassar uses a sustainable online system. Therefore, in-depth socialization is needed so that all parties served and the parties served can optimize the online system.